Pelatihan Penyusunan Dokumen Administrasi Perkantoran dan Etika Pelayanan Prima sebagai Bekal Kesiapan Dunia Kerja bagi Siswa SMK Negeri 1 Sinjai - A. Hadijah Sulfiyani A.; Nasir Nasir; Sri Yunita Simanjutak; Elfira Elfira; Moh. Badrut Tamam (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
The rapid development of the business and industrial sectors requires vocational high school graduates to possess not only technical competencies in office administration but also professional attitudes and excellent service skills. This community service activity aimed to improve students' competencies in preparing office administration documents and implementing excellent service ethics as preparation for entering the workforce. The activity was conducted at SMK Negeri 1 Sinjai using training, demonstrations, simulations, and mentoring methods involving 35 students from the Office Management and Business Services Department. The implementation consisted of preliminary assessment, material presentation, practical exercises, simulations, evaluation, and reflection. The evaluation results indicated significant improvement in students' understanding and practical abilities. The average pre-test score increased from 61.20 to 86.45 in the post-test. Furthermore, students demonstrated improved competence in preparing official letters, meeting minutes, incoming and outgoing mail management, agenda books, disposition sheets, and professional communication during service simulations. The participants also showed greater confidence, discipline, teamwork, and customer-oriented attitudes. This program contributes to strengthening vocational competencies aligned with workplace demands while supporting the implementation of the Merdeka Curriculum in vocational education.